Provável bruxismo do sono e perfil cronotipo entre adolescentes de Belo Horizonte - Sara Oliveira Aguiar (2019)
Sleep bruxism (SB) is characterized by the behavior of clenching and/or grinding of the teeth, with emotional factors and the circadian cycle having a strong influence on the condition. The disagreement between individual preference for day or night (chronotype) and daily activities may favor the occurrence of bruxism. The objective of this cross-sectional study was to evaluate the association between probable SB and chronotype profile among adolescent from Belo Horizonte, Minas Gerais. A total of 435 adolescents, aged 12 to 19 years old, without syndromes and/or neurological disorders, who were regularly enrolled in public and private schools, and their parents/caregivers participated in the study that was approved by the institutional Ethics Committee on Human Research (CAAE: 91561018.5.0000.5149). Parents/caregivers responded a questionnaire designed to gather information about their child's sleeping habits. The adolescents answered two questionnaires. The first contained questions about sleeping habits, characteristics of sleep, and self-report of bruxism and was elaborated according to the proposed by the Consensus of Bruxism. The second questionnaire was The Circadian Energy Scale (CIRENS) for classification of the chronotype profile. Subsequently, extraoral and intraoral clinical examinations were performed in the schools’ rooms, by a previously calibrated examiner, to identify clinical signs and symptoms potentially associated with probable SB. The probable SB was measured according to a scale that considers the presence and severity of clinical signs and symptoms and the frequency of BS. In the scale, higher scores meant a greater severity of probable BS. Data analysis included descriptive statistics and Poisson regression (p<0.05). The prevalence of probable SB was 21.1%. The intermediate chronotype was the most prevalent (83.1%), followed by the morningness profile (9.7%) and the eveningness profile (7.2%). The occurrence of probable SB was not statistically associated with chronotype profiles. The adjusted Poisson regression model revealed that participants who reported having nightmares at least once per week (PR: 4.725, 95% CI: 1.517–14.717) or once per month (PR: 3.595, 95% CI: 1.149–11.247), drooling on the pillow during sleep several times per night (PR: 1.841, 95% CI: 1.017–3.334), and having a lower energy level during the day (PR: 0.876, 95% CI: 0.774–0.992) had a higher severity of probable BS. This study concluded that probable SB was more prevalent among adolescents who reported having nightmares, who drool on the pillow during sleep, and who have lower daily energy levels. In this sample, the probable SB was not associated with the chronotype profiles